Solid compositions and methods for their manufacture
Patent Information
- Application Number
- CN202580021710.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-26
- Filing Date
- 2025-03-18
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]但是,它们中大多是水难溶性物质,口服摄取到体内后的吸收效率低
[0022]若为本发明实施方式的固体组合物,则能够提高水难溶性有机化合物在水中的溶解性。
Smart Images

Figure CN122995860A_ABST
Abstract
Description
Technical Field
[0001] Embodiments of the present invention relate to solid compositions and methods for manufacturing the same. Background Technology
[0002] Polyphenols are known to have antioxidant properties that prevent arteriosclerosis and cerebral infarction. In addition, carotenoids, retinoids, and steroids are known to have antioxidant and other physiological effects. Therefore, their application in the pharmaceutical and medical fields, as well as in the food additive field, is anticipated.
[0003] However, most of these are poorly soluble in water, resulting in low absorption efficiency after oral ingestion. To improve absorption in the digestive tract, it is necessary to increase their solubility in water. As a solution to this problem, it is known to transform crystalline, poorly soluble organic compounds from a crystalline state into an amorphous state.
[0004] For example, Patent Document 1 discloses a solid composition comprising an amorphous, water-insoluble polyphenol, a hydrophilic polymer, and a nonionic surfactant. It also describes the use of polyvinylpyrrolidone as the hydrophilic polymer and sucrose fatty acid esters with an HLB value of 10 or higher as the nonionic surfactant.
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: International Publication No. 2017 / 061627 Summary of the Invention
[0008] The technical problem that the invention aims to solve
[0009] The purpose of this invention is to provide a solid composition that can improve the solubility of a water-insoluble organic compound with high crystallinity in water.
[0010] Technical means for solving problems
[0011] The present invention includes the embodiments shown below.
[0012] [1] A solid composition comprising, in a mixed state: a solid dispersion having a water-soluble polymer as an inert carrier, wherein a crystalline, water-insoluble organic compound is dispersed in the water-soluble polymer in an amorphous state; and a sucrose fatty acid ester having a monoester ratio of 85% by mass or more.
[0013] [2] According to the solid composition of [1], wherein the water-insoluble organic compound is at least one selected from the group consisting of curcuminoids, flavonoids, phenylpropanoids, stilbene, phenolic acids, carotenoids, retinoids, steroids, alkaloids, ceramides and limonenes.
[0014] [3] The solid composition according to [1], wherein the water-insoluble organic compound is at least one selected from the group consisting of curcuminoids, flavanones, flavonols, lignans, coumarins, stilbenes, phenolic acids, luteinoids, retinoids, phytosterols, alkaloids, glucosylceramides and limonenes.
[0015] [4] The solid composition according to any one of [1] to [3], wherein the water-soluble polymer comprises at least one selected from the group consisting of cellulose ether, cellulose ester, homopolymer of N-vinyl lactam, copolymer of N-vinyl lactam, polyalkylene glycol, polyepoxide and poly(meth)acrylate.
[0016] [5] The solid composition according to any one of [1] to [4], wherein the mass ratio of the above-mentioned sucrose fatty acid ester to the above-mentioned water-insoluble organic compound is 0.2 to 30.
[0017] [6] The solid composition according to any one of [1] to [5], wherein the mass ratio of the water-soluble polymer to the sucrose fatty acid ester is 0.1 to 10.
[0018] [7] The solid composition according to any one of [1] to [6], wherein the mass ratio of the sucrose fatty acid ester to the solid dispersion is 0.1 to 3.
[0019] [8] An oral composition comprising any one of the solid compositions described in [1] to [7].
[0020] [9] A method for manufacturing a solid composition, comprising: using a crystalline, water-insoluble organic compound and a water-soluble polymer to obtain a solid dispersion in which the water-insoluble organic compound is dispersed in the water-soluble polymer in an amorphous state; and mixing the solid dispersion with a sucrose fatty acid ester in a ratio of 85% by mass or more of monoester.
[0021] Invention Effects
[0022] If it is a solid composition according to the embodiments of the present invention, it can improve the solubility of water-insoluble organic compounds in water. Attached Figure Description
[0023] [ Figure 1 XRD pattern of the solid composition of Comparative Example 1
[0024] [ Figure 2 XRD pattern of the solid composition of Comparative Example 2
[0025] [ Figure 3XRD pattern of the solid composition of Comparative Example 4
[0026] [ Figure 4 XRD pattern of the solid composition of Comparative Example 6
[0027] [ Figure 5 XRD pattern of the solid composition of Comparative Example 7
[0028] [ Figure 6 XRD pattern of the solid composition of Comparative Example 8
[0029] [ Figure 7 XRD pattern of the solid composition of Comparative Example 9
[0030] [ Figure 8 XRD pattern of the solid composition of Comparative Example 11
[0031] [ Figure 9 XRD pattern of the solid composition of Comparative Example 12
[0032] [ Figure 10 XRD pattern of the solid composition of Comparative Example 16
[0033] [ Figure 11 XRD pattern of the powder before the addition of sucrose fatty acid esters in Example 7 (the powder obtained by vacuum drying and sieving). Detailed Implementation
[0034] The solid composition of this embodiment contains a solid dispersion and a sucrose fatty acid ester in a mixed state. The solid dispersion is obtained by dispersing a crystalline, water-insoluble organic compound in an amorphous state within a water-soluble polymer as an inert carrier. The monoester ratio of the sucrose fatty acid ester is 85% by mass or more. Therefore, the solid composition of this embodiment contains: (A) a crystalline, water-insoluble organic compound obtained by amorphization, (B) a sucrose fatty acid ester, and (C) a water-soluble polymer.
[0035] [(A) Obtained by amorphization of water-insoluble organic compounds]
[0036] (A) A substance obtained by amorphizing a crystalline, water-insoluble organic compound, that is, a substance formed by amorphizing an organic compound that was originally crystalline and therefore insoluble (including insoluble) in water. It is also called an amorphous, water-insoluble organic compound. Here, the solubility (maximum concentration) of the crystalline, water-insoluble organic compound (in its state before amorphization) in pure water at 25°C is less than 1 mg / mL, less than 100 μg / mL, less than 10 μg / mL, or less than 1 μg / mL.
[0037] In this embodiment, specific examples of water-insoluble organic compounds can be cited as follows:
[0038] (A1) Curcumin derivatives: such as curcumin, demethoxycurcumin, bisdemethoxycurcumin, tetrahydrocurcumin;
[0039] (A2) Polyphenols: For example, flavanones (e.g., hesperidin, norihesperidin, sudachitin, naringin, naringin, naringin, hesperidin), flavonols (e.g., myricetin, quercetin, tylosin, silybin), rutin, isoquercitrin, galangal, kaempferol, lacquer yellow Hypericin, flavonoids (e.g., luteolin, apigenin, baicalin, scutellarin, 5,7-dimethoxyflavonoids, diosmin, geraniol, flavonols), flavanols (e.g., catechins, epicatechin, theaflavins, epicatechin gallate, epigallocatechin, epigallocatechin gallate, proanthocyanidins), isoflavones (e.g., genistein), and isoflavones (e.g., genistein). Flavonoids include daidzein, equol, puerarin, and epoetin; anthocyanins (e.g., cyanidin, delphinidin, malvatin, stigmocyanin, methyl anthocyanin), proanthocyanidins, and oligomeric proanthocyanidins (OPC); lignans (e.g., sesamin, sesamolin, sesamol, sesaminol), coumarins (e.g., hesperidin, umbelliferone, coumarin), and phenylpropanoids; stilbene compounds such as resveratrol; phenolic acids such as chlorogenic acid, hydroxycinnamic acid (e.g., caffeic acid), hydroxybenzoic acid (e.g., gallic acid, ellagic acid), and rosmarinic acid; and xanthones (e.g., α-mangosteen), isoflavone diols (e.g., equol), gingerol, shogaol, and gingerone.
[0040] (A3) Carotenoids: For example, lutein (e.g., astaxanthin, lutein, β-cryptoxanthin, zeaxanthin, neoxanthin), carotene (e.g., β-carotene, lycopene);
[0041] (A4) Retinoids: such as retinoic acid, retinol, retinaldehyde, adapalene, tamibarbitine;
[0042] (A5) Steroids: For example, phytosterols (e.g., β-sitosterol, stigmasterol, campesterol, brassicasterol, 7-ergosterol, isoflavone, 7-stigmasterol, alfalfa, diosgenin, ginsenosides), vitamin D (e.g., ergocalciferol, cholecalciferol);
[0043] (A6) Alkaloids: such as berberine, morphine, capsaicin;
[0044] (A7) Ceramides: for example, glucosylceramides, human ceramides, synthetic ceramides; and
[0045] (A8) Limonoids: such as limonin and azadirachtin.
[0046] They can be used individually or in combination with two or more. It should be noted that in this specification, the terms "curcumin", "polyphenol", "carotenoid", "retinoid", "steroid", "alkaloid", "ceramide" and "limonene" are used in the context of including derivatives such as aglycones, acetylates, fatty acid esters, amidates, malonylates, methylates, polymers, condensates, salts, and glycosides.
[0047] Preferably, the water-insoluble organic compound is at least one selected from the group consisting of curcuminoids, flavonoids, phenylpropanoids, stilbenes, phenolic acids, carotenoids, retinoids, steroids, alkaloids, ceramides, and limonenes. More preferably, the water-insoluble organic compound is at least one selected from the group consisting of curcuminoids, flavanones, flavonols, lignans, coumarins, stilbenes, phenolic acids, luteinoids, retinoids, phytosterols, alkaloids, glucosylceramides, and limonenes. Even more preferably, the water-insoluble organic compound is at least one selected from the group consisting of curcuminoids, flavanones, flavonols, and lutein, and even more preferably, at least one selected from the group consisting of curcumin, hesperidin, myricetin, and astaxanthin.
[0048] The solid composition of this embodiment comprises an amorphous, water-insoluble organic compound. The amorphous state of the water-insoluble organic compound can be confirmed by the absence of distinct diffraction peaks in X-ray diffraction (XRD). The solid composition may contain both an amorphous and a crystalline form of the water-insoluble organic compound. However, the amount of the crystalline form of the water-insoluble organic compound is preferably as small as possible, preferably substantially or completely absent.
[0049] The content of the amorphous, water-insoluble organic compound in the solid composition is not particularly limited, but is preferably 1% to 50% by mass, more preferably 3% to 40% by mass, even more preferably 4% to 40% by mass, even more preferably 5% to 30% by mass, and even more preferably 6% to 20% by mass.
[0050] [(B) Sucrose fatty acid esters]
[0051] (B) The component is a sucrose fatty acid ester with a monoester ratio of 85% or more. Sucrose fatty acid esters are formed by esterification of fatty acids with the hydroxyl groups of sucrose. One molecule of sucrose has eight hydroxyl groups, and depending on the number of fatty acids esterified, there are monoesters to octaesters. In this embodiment, a substance is used in which the ratio of a monoester formed by the bonding of a fatty acid with one hydroxyl group to a sucrose fatty acid ester is 85% or more out of 100% by mass. In typical sucrose fatty acid esters, the monoester ratio is 80% or less; in contrast, this embodiment uses a sucrose fatty acid ester with a monoester ratio as high as 85% or more. This improves the solubility of water-insoluble organic compounds in water.
[0052] The ratio of monoesters in sucrose fatty acid esters is preferably 90% by mass or more, more preferably 95% by mass or more, even more preferably 97% by mass or more, even more preferably 99% by mass or more, and can be 100% by mass. Therefore, the ratio of diesters or more esters is preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 3% by mass or less, and even more preferably 1% by mass or less.
[0053] The ratio of monoesters in sucrose fatty acid esters can be determined by analyzing the ester distribution of sucrose fatty acid esters using GPC (gel filtration chromatography). This ratio can be calculated as the ratio of the peak area derived from monoesters to the total peak area. The analytical conditions for GPC are described below.
[0054] <GPC Conditions>
[0055] • Device: LC-6A, manufactured by Shimadzu Corporation
[0056] • Pillar: "Megapak GEL201" manufactured by Nippon Seikatsu Co., Ltd.
[0057] Solvent: THF
[0058] • Flow rate: 3 mL / min
[0059] • Sample concentration: 6% by volume
[0060] • Sample injection volume: 50 μL
[0061] Column temperature: 25℃
[0062] The sucrose fatty acid ester preferably contains fatty acids with 12 to 22 carbon atoms as its constituent fatty acids. That is, as the fatty acids constituting the sucrose fatty acid ester, saturated or unsaturated, straight-chain or branched fatty acids with 12 to 22 carbon atoms are preferably used, and one or more of them can be used. The constituent fatty acids are preferably mainly composed of fatty acids with 12 to 22 carbon atoms, more preferably mainly composed of fatty acids with 14 to 18 carbon atoms, and even more preferably mainly composed of fatty acids with 16 to 18 carbon atoms. Here, "main component" means that relative to 100% by mass of the constituent fatty acids, it is 50% by mass or more, more preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more, and can be 100% by mass.
[0063] The constituent fatty acids of sucrose fatty acid esters are preferably saturated fatty acids, and more preferably straight-chain saturated fatty acids. In a preferred embodiment, the constituent fatty acid is mainly stearic acid, and a mixture of stearic acid and palmitic acid is preferred.
[0064] There is no particular limitation on the HLB value of sucrose fatty acid esters; it can be 10 or higher, 13 or higher, or 16 or higher.
[0065] [(C) Water-soluble polymers]
[0066] (C) The water-soluble polymer of the component is a natural or synthetic polymer that is soluble in water. The solubility of the water-soluble polymer in water is preferably 0.001% by mass or more, more preferably 0.1% by mass or more, and may also be 1% by mass or more, relative to pure water at 25°C (maximum solubility concentration).
[0067] Specific examples of water-soluble polymers include:
[0068] • Homopolymers and copolymers of N-vinyl lactams, such as polyvinylpyrrolidone (PVP), copolyvinylpyrrolidone (i.e., copolymers of N-vinylpyrrolidone and vinyl acetate), and copolymers of N-vinylpyrrolidone and vinyl propionate.
[0069] Cellulose ethers such as alkyl cellulose (e.g., methyl cellulose, ethyl cellulose), hydroxyalkyl cellulose (e.g., hydroxypropyl cellulose (HPC)), and hydroxyalkylalkyl cellulose (e.g., hydroxypropyl methyl cellulose (HPMC), hydroxyethyl methyl cellulose (HEMC));
[0070] Cellulose esters such as cellulose phthalate, cellulose acetate, hydroxypropyl methyl cellulose phthalate (HPMCP), hydroxypropyl methyl cellulose succinate, and hydroxypropyl methyl cellulose acetate succinate (HPMCAS);
[0071] Polyalkylene glycols (PAGs), such as polyethylene glycol (PEG) and polypropylene glycol (PPG), have structures corresponding to polymers of alkylene glycols with 2 to 4 carbon atoms;
[0072] Polyethylene oxide (PEO), polypropylene oxide (PPO), copolymers of ethylene oxide and propylene oxide, etc. (PAO);
[0073] • Poly(meth)acrylates such as methacrylate / ethyl acrylate copolymer, methacrylate / methyl methacrylate copolymer, butyl methacrylate / 2-dimethylaminoethyl methacrylate copolymer, poly(hydroxyalkyl acrylate), poly(hydroxyalkyl methacrylate), alkyl methacrylate / 2-dimethylaminoethyl methacrylate copolymer, alkyl methacrylate / methacrylate copolymer, alkyl methacrylate / methyl methacrylate copolymer, alkyl methacrylate / methacryloyloxyethyltrimethylammonium chloride copolymer, etc.
[0074] • Polyvinyl caprolactam / polyvinyl acetate / polyethylene glycol graft copolymer;
[0075] • Polyacrylamide;
[0076] Polyvinyl alcohol;
[0077] Starch, modified starch, processed starch, and other starches and their derivatives;
[0078] • Dextrin, modified dextrin, processed dextrin, and other dextrins and their derivatives; and
[0079] Oligosaccharides and polysaccharides such as carrageenan, galactomannan, xanthan gum, and gum arabic can be used. Any one of them can be used, or two or more can be used in combination. It should be noted that polyalkylene glycols and polyepoxides are compounds with essentially the same structure. This application uses substances known to those skilled in the art as follows: the former is a substance with an average molecular weight of less than approximately 20,000, and the latter is a substance with a larger molecular weight.
[0080] Of which, as a water-soluble polymer, at least one (C1) selected from the group consisting of cellulose ethers, cellulose esters, homopolymers of N-vinyllactams, copolymers of N-vinyllactams, polyalkylene glycols, polyepoxides, and poly(meth)acrylates is preferred; more preferably, at least one (C2) selected from the group consisting of homopolymers of cellulose ethers, cellulose esters, N-vinyllactams, and copolymers of N-vinyllactams is preferred. In this case, in 100% by mass of the water-soluble polymer, the content of the at least one (C1) or (C2) is preferably 70% to 100% by mass, more preferably 80% to 100% by mass, more preferably 90% to 100% by mass, and even more preferably 95% to 100% by mass.
[0081] In one embodiment, the water-soluble polymer preferably contains at least one (C3) selected from the group consisting of hydroxypropyl cellulose, hydroxypropyl methylcellulose, polyvinylpyrrolidone, and polyethylene glycol; more preferably, the water-soluble polymer contains at least one (C4) selected from the group consisting of hydroxypropyl cellulose, hydroxypropyl methylcellulose, and polyvinylpyrrolidone. Alternatively, the water-soluble polymer may contain at least one (C5) selected from the group consisting of hydroxypropyl cellulose, hydroxypropyl methylcellulose, polyvinylpyrrolidone, hydroxypropyl methylcellulose phthalate, and hydroxypropyl methylcellulose acetate succinate. In 100% by mass of the water-soluble polymer, the content of the at least one (C3), (C4), or (C5) is preferably 70% to 100% by mass, more preferably 80% to 100% by mass, more preferably 90% to 100% by mass, and even more preferably 95% to 100% by mass.
[0082] The molecular weight of water-soluble polymers is not particularly limited; for example, the weight-average molecular weight (Mw) can be 1,000–600,000, 1,000–100,000, 5,000–80,000, or 10,000–60,000. Here, the weight-average molecular weight (Mw) is a value determined by the GPC method.
[0083] The K value of water-soluble polymers is not particularly limited, but is preferably 5 to 100, preferably 10 to 70, preferably 15 to 50, and preferably 15 to 35. The K value is a value representing molecular weight obtained based on the Fikentscher method and can be determined by known determination methods and the Fikentscher formula below.
[0084] K value = { [300ClogZ+(C+1.5ClogZ) ] 2 ] 1 / 2 +1.5ClogZ-C} / (0.15C+0.003C) 2 )
[0085] In the formula, C represents the concentration of the sample (mass%), and the K value of PVP in the following examples was determined with a sample concentration of 1 mass%. Z represents the relative viscosity (ηrel) of the solution at concentration C. The relative viscosity ηrel is obtained by the following formula.
[0086] ηrel = (flow time of the solution) ÷ (flow time of the water)
[0087] In one embodiment, hydroxyalkyl cellulose such as HPC can be used as the water-soluble polymer. In this case, the viscosity (20°C) of the hydroxyalkyl cellulose when prepared as a 2% by mass aqueous solution is preferably 0.1 to 10000 mPa·s, more preferably 0.3 to 5000 mPa·s, more preferably 0.3 to 3000 mPa·s, more preferably 0.3 to 1000 mPa·s, more preferably 0.5 to 500 mPa·s, more preferably 0.8 to 100 mPa·s, more preferably 1 to 20 mPa·s, more preferably 1.2 to 10 mPa·s, more preferably 1.5 to 8 mPa·s, and more preferably 1.8 to 4 mPa·s. This viscosity is determined according to the rotational viscometer method of the Ninth Edition of the Food Additives Standard.
[0088] Furthermore, as hydroxyalkyl cellulose, the weight-average molecular weight (Mw) is 1,000 to 600,000, more preferably 2,000 to 500,000, more preferably 3,000 to 400,000, more preferably 5,000 to 300,000, more preferably 10,000 to 200,000, more preferably 15,000 to 150,000, more preferably 20,000 to 100,000, more preferably 25,000 to 80,000, and more preferably 30,000 to 50,000. Here, the weight-average molecular weight (Mw) is a value determined by the GPC method.
[0089] Furthermore, in hydroxyalkyl cellulose, the degree of substitution of hydroxyalkoxy (hydroxypropoxy in the case of HPC) is preferably 5% to 99% by mass, more preferably 10% to 95% by mass, even more preferably 15% to 90% by mass, and even more preferably 20% to 85% by mass. Here, the degree of substitution is determined by gas chromatography according to the determination method described in the ninth edition of the Food Additives Code for hydroxypropyl cellulose.
[0090] In one embodiment, hydroxypropyl methylcellulose phthalate (HPMCP) can be used as a water-soluble polymer. In this case, the viscosity of HPMCP obtained according to the determination method described in the 18th revised Japanese Pharmacopoeia, "Hydroxypropyl Methylcellulose Phthalate," is preferably 10 to 200 mPa·s, more preferably 20 to 100 mPa·s, and even more preferably 30 to 50 mPa·s.
[0091] In addition, the weight-average molecular weight Mw determined by HPMCP using the SEC-MALS method (size exclusion chromatography-multi-angle light scattering method) is preferably 10,000 to 200,000, more preferably 20,000 to 100,000, and even more preferably 30,000 to 60,000.
[0092] Here, the conditions for the SEC-MALS method used in HPMCP are as follows.
[0093] Column: ShodexOHpak SB-806MHQ manufactured by Lenovo Co., Ltd.
[0094] Elution buffer: 0.10 mol / L acetate buffer / DMF = 9 / 1 (v / v) mixture (acetic buffer is prepared using sodium acetate, acetic acid and sodium chloride)
[0095] Flow rate: 1.0 mL / min
[0096] Sample concentration: 0.1 w / v%
[0097] Injection volume: 0.1 mL
[0098] Detector: DAWN manufactured by Wyatt Technology Co., Ltd., and Shodex RI-71 manufactured by Resonack Co., Ltd.
[0099] In addition, HPMCP preferably contains 1% to 60% carboxybenzoyl group, more preferably 10% to 50%, and even more preferably 20% to 40%, as determined by the method described in the 17th edition of the Japanese Pharmacopoeia for "hydroxypropyl methylcellulose phthalates".
[0100] In one embodiment, hydroxypropyl methylcellulose acetate succinate (HPMCAS) can be used as the water-soluble polymer. In this case, the viscosity of HPMCAS, measured according to the determination method described in the 18th revised edition of the Japanese Pharmacopoeia "Hydroxypropyl methylcellulose acetate succinate" (the viscosity of a 100g solution obtained by adding 2g of HPMCAS to a dilute sodium hydroxide solution and measuring it at 20°C), is preferably 1 to 200 mPa·s, more preferably 1 to 50 mPa·s, and even more preferably 1 to 10 mPa·s.
[0101] In addition, the weight-average molecular weight Mw of HPMCAS, as determined by the SEC-MALS method, is preferably 1,000 to 200,000, more preferably 5,000 to 100,000, and even more preferably 10,000 to 30,000.
[0102] Here, the Mw of HPMCAS is calculated as follows: the Mw of hydroxypropyl methylcellulose (HPMC), which forms its backbone, is determined by the SEC-MALS method under the following conditions, and the degree of polymerization is then multiplied by the monomer molecular weight calculated based on the degree of substitution of HPMCAS.
[0103] Column: Shodex OHpak SB-806MHQ manufactured by Lenovo Co., Ltd.
[0104] Eluent: Aqueous solution of sodium hydroxide, potassium dihydrogen phosphate, and dipotassium hydrogen phosphate
[0105] Flow rate: 1.0 mL / min
[0106] Sample concentration: 0.2 w / v%
[0107] Injection volume: 0.1 mL
[0108] Detector: DAWN manufactured by Wyatt Technology Co., Ltd., and Shodex RI-71 manufactured by Resonack Co., Ltd.
[0109] Furthermore, the amount of methoxy group determined by HPMCAS based on the method described in the 18th revised Japanese Pharmacopoeia for "hydroxypropyl methylcellulose acetate succinate" is preferably 10% to 40%, more preferably 20% to 30%. The amount of hydroxypropoxy group is preferably 1% to 20%, more preferably 3% to 10%. The amount of acetyl group is preferably 1% to 30%, more preferably 5% to 15%. The amount of succinyl group is preferably 1% to 30%, more preferably 5% to 15%.
[0110] [Solid Composition]
[0111] In the solid composition of this embodiment, the water-insoluble organic compound of component (A) and the water-soluble polymer of component (C) constitute solid dispersion (D), which exists in a mixed state with sucrose fatty acid ester of component (B) through mixing of powders. That is, the powder of solid dispersion (D) containing components (A) and (C) is mixed with the powder of component (B).
[0112] The solid dispersion is formed by using a water-soluble polymer as an inert carrier, in which a water-poorly soluble organic compound is dispersed at the molecular level. The water-soluble polymer enters the intermolecular space of the water-poorly soluble organic compound, causing the crystalline structure of the compound to disintegrate and the compound to become amorphous. Typically, in a solid dispersion, the water-poorly soluble drug undergoes amorphization, and the amorphous solid water-poorly soluble drug is dispersed at the molecular level in an inert carrier, thus readily dissolving in water. Particularly in this embodiment, the specific sucrose fatty acid ester is powdered and mixed using post-mixing, thereby significantly improving the solubility of the water-poorly soluble organic compound in water.
[0113] The solid composition of this embodiment is solid at room temperature (25°C), and more specifically, it remains solid even after being left at room temperature for more than 5 hours.
[0114] In the solid composition, the mass ratio of (B) sucrose fatty acid ester to (A) amorphous water-insoluble organic compound, i.e., the mass ratio (B) / (A), is preferably 0.2 to 30, more preferably 0.5 to 20, even more preferably 1.0 to 15, even more preferably 1.5 to 12, even more preferably 2.0 to 10, even more preferably 2.5 to 8.0, and even more preferably 3.0 to 6.0.
[0115] In the solid composition, the mass ratio of the water-soluble polymer (C) to the mass of the amorphous, water-insoluble organic compound (A), i.e., the mass ratio (C) / (A), is preferably 0.2 to 30, more preferably 0.5 to 25, even more preferably 1.0 to 20, even more preferably 2.0 to 15, even more preferably 3.0 to 12, even more preferably 3.5 to 10, and even more preferably 4.0 to 9.0.
[0116] In the solid composition, the mass ratio of the water-soluble polymer (C) to the sucrose fatty acid ester (B), i.e., the mass ratio (C) / (B), is preferably 0.1 to 10, more preferably 0.2 to 8.0, even more preferably 0.3 to 5.0, further preferably 0.5 to 4.0, even more preferably 1.0 to 3.0, and may also be 1.0 to 2.5.
[0117] In the solid composition, the mass ratio of (B) sucrose fatty acid ester to the mass of (D) solid dispersion, i.e., the mass ratio (B) / (D), is preferably 0.1 to 3, more preferably 0.2 to 2, and even more preferably 0.3 to 1.0.
[0118] In addition to the components (A) to (C) described above, the solid composition of this embodiment may also contain other components. These other components are not particularly limited, but examples include: excipients, binders, fillers, lubricants, extenders, disintegrants, surfactants, seasonings, and flavorings.
[0119] In one embodiment, the solid composition may contain sugars, sugar alcohols, starches, dextrins, crystalline cellulose, etc., as excipients. By incorporating excipients, the solubility in water can be further improved. The excipients are preferably incorporated into the solid composition by powder mixing of the above-described (D) solid dispersion and (B) sucrose fatty acid ester.
[0120] Specific examples of the sugars and / or sugar alcohols mentioned above include lactose, sucrose, glucose, maltose, xylose, trehalose, mannitol, sorbitol, xylitol, erythritol, maltitol, etc., and any one of them may be used, or two or more may be used together.
[0121] The amount of the excipients is not particularly limited. For example, relative to the total amount of (A) to (C) above, 10 to 500 parts by mass, 50 to 400 parts by mass, or 100 to 300 parts by mass, can be used.
[0122] The form of the solid composition is not particularly limited; it can be in powder form or in granule form formed by granulating the powder, and can take various forms of solid dosage forms.
[0123] [Method for manufacturing solid compositions]
[0124] The method for manufacturing the solid composition of this embodiment is not particularly limited. In one embodiment, the method for manufacturing the solid composition includes the following steps.
[0125] (1) A process of obtaining a solid dispersion of a water-insoluble organic compound in an amorphous state within a water-soluble polymer using a crystalline, water-insoluble organic compound and a water-soluble polymer; and
[0126] (2) A process of mixing the obtained solid dispersion with a sucrose fatty acid ester in a ratio of 85% by mass or more of monoester.
[0127] In step (1), the method of manufacturing the solid dispersion is not particularly limited. For example, it can be (1-1) dissolving a water-insoluble organic compound and a water-soluble polymer in a solvent to prepare a solution and removing the solvent from the solution, or it can be (1-2) thermally melting the water-insoluble organic compound and the water-soluble polymer.
[0128] In the method described in (1-1) above, the solvent used is not particularly limited to solvents capable of dissolving water-insoluble organic compounds and water-soluble polymers. Specific examples of solvents include: alcohols such as methanol, ethanol, 1-propanol, isopropanol, 1-butanol, and 2-butanol; ketones such as methyl ethyl ketone and acetone; acetates such as ethyl acetate and methyl acetate; ethers such as diethyl ether; alkanes such as propane, butane, and hexane; polyols such as propylene glycol and glycerol; chlorinated hydrocarbons such as dichloromethane, chloroform, and dichloroethane; and organic solvents such as cyclohexane. Any one or a mixture of two or more of these solvents can be used. Alternatively, mixtures of these organic solvents and water can also be used.
[0129] In the method described in (1-1) above, the water-insoluble organic compound and the water-soluble polymer can be dissolved simultaneously by heating the solvent. The water-insoluble organic compound can be dissolved in the solvent first, and then the water-soluble polymer can be added and dissolved; the order of dissolution is not limited. During dissolution, stirring or ultrasonic vibration using an ultrasonic device is preferred. The temperature at which the solvent is heated is not particularly limited, but is preferably 60–90°C.
[0130] In the solution prepared by the method described in (1-1) above, the concentration of each component is not particularly limited. For example, the concentration of the water-insoluble organic compound can be 0.1% to 5% by mass, or 0.2% to 3% by mass. The concentrations of the water-soluble polymers can be set according to the mass ratio (C) / (A) of the above-mentioned components in the manufactured solid composition.
[0131] In one embodiment, when astaxanthin is used as a poorly water-soluble organic compound, it can be isomerized by aging it in an organic solvent.
[0132] In the method described in (1-1) above, there is no particular limitation on the method for removing the solvent from the solution; examples include vacuum drying, spray drying, freeze drying, heat drying, and natural drying. After removing the solvent, the solution can be pulverized.
[0133] In step (2), as a method of mixing the solid dispersion with sucrose fatty acid ester, there are no particular limitations as long as the powders are mixed together without the use of a solvent.
[0134] [Uses of Solid Compositions]
[0135] The solid composition of this embodiment is suitable for use in pharmaceuticals, quasi-pharmaceuticals, health functional foods (e.g., foods for specific health purposes, nutritional functional foods, functional display foods, etc.), health foods, nutritional supplements, nutritional supplements, pet food, cosmetics, and other applications. It is preferably used as an oral formulation. That is, an oral composition of a preferred embodiment contains the above-described solid composition.
[0136] The oral composition may consist solely of the solid composition described above, or it may contain other food ingredients, other active ingredients, and / or additives together with the solid composition. Examples of additives include, for instance, excipients, binders, fillers, lubricants, extenders, disintegrants, surfactants, flavorings, fragrances, and colorings.
[0137] There are no particular limitations on the form of oral compositions, such as tablets, granules, powders, fine granules, pills, and capsules.
[0138] Since the solid composition of this embodiment contains poorly soluble organic compounds that have excellent solubility in water, it is expected that the poorly soluble organic compounds will have high solubility in body fluids when administered orally or ingested, thus enabling efficient absorption of the poorly soluble organic compounds.
[0139] Example
[0140] The present invention will now be described in more detail based on embodiments and comparative examples, but is not limited thereto.
[0141] The details of the components in Tables 1 to 3 are as follows.
[0142] • CUR: Curcumin, manufactured by Fuji Film Wako Pure Pharmaceutical Co., Ltd., Wako Premium Grade
[0143] ·HPT: Hesperetin, "Hesperetin" manufactured by Fujifilm Chemical Co., Ltd., supplier: Fujifilm Wako Pure Chemical Co., Ltd.
[0144] • MIR: Myricetin, manufactured by Combi-Blocks, 3,3',4',5,5',7-Hexahydroxyflavone, supplier: Fujifilm Wako Pure Chemicals Co., Ltd., product code QA-0360
[0145] • AST: Astaxanthin, manufactured by Combi-Blocks, Beta-Carotene-4,4'-dione, Supplier: Fujifilm Wako Pure Chemicals Co., Ltd., Product Code QA-1399
[0146] • SE-SS: "DK Ester SS" manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd. is a sucrose fatty acid ester whose main component is stearic acid with 18 carbon atoms. The monoester ratio is 99% by mass, with the remaining portion consisting of diesters and triesters at a ratio of 1% by mass. HLB=19
[0147] • SE-F160: DK Ester F-160, manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., is a sucrose fatty acid ester whose main component is stearic acid with 18 carbon atoms. The monoester ratio is 70% by mass, with the remaining portion consisting of diesters and triesters at a ratio of 30% by mass. HLB=15
[0148] • SE-F50: DK Ester F-50, manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., is a sucrose fatty acid ester whose main component is stearic acid with 18 carbon atoms. The monoester ratio is 30% by mass, and the remaining portion consists of 70% by mass of diesters or higher. HLB=6
[0149] • PVP: Polyvinylpyrrolidone "Ifitack K-30PH" manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd. (weight average molecular weight 45,000, K value = 30)
[0150] • HPC: Hydroxypropyl cellulose "CELNY SSL" manufactured by Nippon Soda Co., Ltd. (viscosity 2.0~2.9 mPa·s (20℃, 2% by mass aqueous solution), weight average molecular weight 40000)
[0151] HPMCAS: Hydroxypropyl methyl cellulose acetate succinate "Shin-EtsuAQOAT AS-MG" manufactured by Shin-Etsu Chemical Industry Co., Ltd. (viscosity 2~4 mPa·s (20℃, 2% by mass solution), weight-average molecular weight 22,400, methoxy group 21%~25%, hydroxypropoxy group 5%~9%, acetyl group 7%~11%, succinyl group 10%~14%)
[0152] HPMCP: Hydroxypropyl methyl cellulose phthalate "HPMCP HP-55" manufactured by Shin-Etsu Chemical Co., Ltd. (viscosity 32~48 mPa·s (20℃, 10% by mass solution), weight-average molecular weight 45,600, carboxybenzoyl 27%~35%)
[0153] [Comparative Example 1]
[0154] The powder obtained by pulverizing curcumin (CUR) using an agate mortar and pestle was used as the solid composition of Comparative Example 1.
[0155] [Comparative Example 2]
[0156] Prepare 40g of curcumin (CUR) as (A) a water-insoluble organic compound, polyvinylpyrrolidone (PVP) as (C) a water-soluble polymer, and a solvent, according to the proportions (parts by mass) shown in Table 1 below. Place them into a 50mL spiral tube, and then perform (1) a heating treatment by immersing the spiral tube in a 75°C hot water bath for 4 minutes, and (2) a ultrasonic treatment by immersing the spiral tube in a bath at 20-50°C for 4 minutes using a small ultrasonic device (manufactured by Yamato Scientific Co., Ltd., "BRANSON 2210") (select "SET SONICS min" and turn it on). Repeat (1) and (2) until all curcumin and PVP are dissolved. For the resulting solution, distill off the solvent using an evaporator. Using the evaporator, reduce the pressure from 400hPa to 160hPa at 75°C to almost eliminate the solvent, and then continue distilling at 10-60hPa for 10-50 minutes. The solid material adhering to the wall of the eggplant-shaped flask was scraped off with a scraper, and the solid material was crushed with an agate mortar to obtain the solid composition of Comparative Example 2. As will be described later, the solid composition of Comparative Example 2 is a solid dispersion. It should be noted that "(C) solid dispersion" in Table 1 refers to the case where a water-soluble polymer constitutes part of the solid dispersion (the same applies to Tables 2 to 6).
[0157] [Comparative Example 3]
[0158] One part by weight of curcumin powder (pulverized using an agate mortar), two parts by weight of sucrose fatty acid ester SE-SS powder, and four parts by weight of PVP powder were mixed on a medicine packaging paper to obtain the solid composition of Comparative Example 3. It should be noted that "(C) Powder Mixing" in Table 1 refers to the case where water-soluble polymers are incorporated into the solid composition through powder mixing (the same applies to Tables 2, 4-6).
[0159] [Example 1]
[0160] According to the proportions (parts by mass) shown in Table 1, (A) curcumin, (B) sucrose fatty acid ester SE-SS, (C) PVP, and solvent were prepared in a total of 40g. The preparation of the solution, distillation of the solvent, and pulverization using a mortar and pestle were performed using curcumin, PVP, and solvent in the same manner as in Comparative Example 2. Sucrose fatty acid ester SE-SS powder was added to the obtained powder and mixed on a pharmaceutical packaging paper to obtain the solid composition of Example 1.
[0161] [Comparative Examples 14 and 15]
[0162] Following the proportions (parts by mass) shown in Table 1, SE-F160 and SE-F50 were used instead of (B) sucrose fatty acid ester SE-SS, respectively, and the other procedures were the same as in Example 1, to obtain the solid compositions of Comparative Examples 14 and 15.
[0163] For the solid compositions of Comparative Examples 1 and 2, X-ray diffraction (XRD) was performed as an evaluation of amorphization. The evaluation method is as follows. It should be noted that, regarding the solid compositions of Examples 1, 14, and 15, since they were obtained by simply mixing sucrose fatty acid esters in powder form prepared in the same manner as Comparative Example 2, the same evaluation method as Comparative Example 2 was used. Furthermore, for the solid composition of Comparative Example 3, since it was obtained by simply mixing sucrose fatty acid esters and water-soluble polymers in powder form with the solid composition of Comparative Example 1, the same evaluation method as Comparative Example 1 was used.
[0164] [Amorphization Evaluation: XRD]
[0165] RINT UltimaIII horizontal goniometer (D / teX-25) manufactured by RIGACK Co., Ltd. was used to obtain XRD patterns of solid compositions. The XRD measurement conditions were: concentrated method, X-ray: Cu / 40kV / 40mA, scan range: 3.0°~50.0°, scan axis: 2θ / θ. Based on the obtained XRD patterns, the amorphization of water-insoluble organic compounds was evaluated according to the following criteria.
[0166] A: It lacks the crystallization peaks characteristic of water-insoluble organic compounds (amorphous state).
[0167] B: The presence of crystallization peaks characteristic of water-insoluble organic compounds (substances containing crystalline material).
[0168] For the solid compositions of Example 1 and Comparative Examples 1-3, 14, and 15, a dissolution test was performed to evaluate their solubility in water. The evaluation method is described below.
[0169] [Dissolution Test: Dissolution Amount]
[0170] As a dissolution test apparatus, the "NTR-6600AST" manufactured by Toyama Sangyo Co., Ltd. was used. 900 mL of deionized water was added to the container, and the mixture was stirred overnight at 37℃ ± 0.2℃ for degassing. Gelatin capsules ("HF Capsules" manufactured by Matsuya Co., Ltd.) containing 15 mg of a solid composition (equivalent to curcumin) were placed in a settling plate and added to the container. After a specified time, samples were taken from the container through a 100 μm filter and filtered through a 0.45 μm membrane filter. The specified time was 30 minutes, 60 minutes, 120 minutes, and 240 minutes. The filtrate was diluted twice with ethanol, filtered through a 0.20 μm membrane filter, and curcumin was quantified by HPLC. Three-point measurements were performed on each solid composition, and the average value was rounded to the third decimal place to determine the dissolution amount. As the aforementioned 100μm filter, the "Porous Pre-Filter Poro Filter30" manufactured by Toyama Sangyosha was used (filter material: ultra-high molecular weight polyethylene, mesh size: 100μm). As the aforementioned 0.45μm membrane filter, the "25HP045AN" manufactured by ADVANTEC was used (filter material: hydrophilic PTFE, mesh size: 0.45μm). Additionally, as the 0.20μm membrane filter, the "13HP020AN" manufactured by ADVANTEC was used (filter material: hydrophilic PTFE, mesh size: 0.20μm). HPLC conditions were as follows: column: octadecylsilane column; mobile phase: a mixture of methanol / 10mM ammonium acetate aqueous solution; wavelength: 430nm.
[0171] The oral absorption of the solid compositions of Example 1 and Comparative Example 1 was evaluated by animal experiments. The evaluation methods are described below.
[0172] [Oral Absorption Evaluation: Animal Experiments]
[0173] Three male SD rats were orally administered a dose of 200 mg / kg of a poorly soluble organic compound (POC). Blood samples were collected at 0.5, 1, 1.5, 2, 3, 4, and 24 hours post-administration. The concentration of the POC in the blood was determined by liquid chromatography-mass spectrometry (LC-MS / MS), and the AUC (area under the blood concentration-time curve) of the POC was calculated. The highest AUC among the three rats was used.
[0174] For LC-MS / MS analysis, as a pretreatment step, 20 μL of plasma sample and 80 μL of acetonitrile were added to a microtube for suspension to remove proteins. After removing proteins by centrifugation, the supernatant was filtered through a filter (Millipore, Ultrafree-MC, Hydrohilic PTFE membrane, 0.2 μm). This solution was then mixed with ultrapure water at a 1:1 (mass ratio) and used as the assay sample. The LC-MS / MS analysis conditions were: column: octadecylsilane column; ion source: ESI+; mobile phase: a mixture of methanol / 10 mM ammonium formate aqueous solution.
[0175] [Table 1]
[0176]
[0177] In Comparative Example 1, such as Figure 1 As shown in the XRD pattern, characteristic peaks of curcumin are present. Therefore, curcumin is in a crystalline state, as shown in Table 1, and did not dissolve in water in the dissolution test.
[0178] In Comparative Example 2, a solid composition was prepared by dissolving curcumin and PVP together in a solvent in a solution, and then removing the solvent from the solution. In the solid composition of Comparative Example 2, as... Figure 2 As shown, the XRD pattern does not show the characteristic peaks of curcumin, indicating that curcumin is in an amorphous state. Therefore, the solid composition of Comparative Example 2 is a solid dispersion containing amorphous curcumin. In Comparative Example 2, the solubility in water was improved compared to Comparative Example 1.
[0179] In Comparative Example 3, curcumin, sucrose fatty acid ester SE-SS, and PVP were mixed in powder form. Simply mixing these three ingredients in powder form did not improve the solubility of curcumin in water.
[0180] In contrast, in Example 1, sucrose fatty acid ester SE-SS was mixed into a solid dispersion containing curcumin and PVP by post-mixing. As a result, the solubility in water was significantly improved not only compared to Comparative Example 1 and Comparative Example 3, which were in a crystalline state, but also compared to Comparative Example 2, which was a solid dispersion.
[0181] On the other hand, in Comparative Examples 14 and 15, sucrose fatty acid esters were mixed into powders by post-mixing, similar to Example 1. However, since they were sucrose fatty acid esters with a low monoester ratio, their solubility in water was poor compared to Example 1.
[0182] Regarding the evaluation of oral absorption based on animal experiments, in Comparative Example 1, the AUC of curcumin was 1 h·ng / mL, compared to 212 h·ng / mL in Example 1, in which sucrose fatty acid ester SE-SS was mixed into a solid dispersion, demonstrating excellent in vivo absorption efficiency after oral ingestion.
[0183] [Comparative Example 4]
[0184] Prepare 40g of curcumin (CUR) as (A) a water-insoluble organic compound, hydroxypropyl cellulose (HPC) as (C) a water-soluble polymer, and a solvent, according to the proportions (parts by mass) shown in Table 2 below. The curcumin and solvent are placed into a 50mL spiral tube, and then subjected to (1) heat treatment by immersing the spiral tube in a 75°C hot water bath for 4 minutes, and (2) ultrasonic treatment by immersing the spiral tube in a small ultrasonic device (manufactured by Yamato Scientific Co., Ltd., "BRANSON 2210") at 20-50°C for 4 minutes (in the above device, select "SET SONICS min" and turn it on). Repeat steps (1) and (2) until the curcumin is completely dissolved. While stirring the obtained solution with a rotor, add HPC and stir until dissolved. Distill off the solvent from the obtained solution using an evaporator. The solvent was distilled off at 75°C from 400 hPa to 160 hPa until almost completely removed using an evaporator, and then further reduced to 10-60 hPa for 10-50 minutes. The solid material adhering to the wall of the eggplant-shaped flask was scraped off with a spatula and pulverized with an agate mortar to obtain the solid composition of Comparative Example 4. As described below, the solid composition of Comparative Example 4 is a solid dispersion.
[0185] [Comparative Example 5]
[0186] One part by weight of curcumin powder (powder pulverized using an agate mortar), four parts by weight of sucrose fatty acid ester SE-SS powder, and four parts by weight of HPC powder were mixed on a medicine packaging paper to obtain the solid composition of Comparative Example 5.
[0187] [Example 2]
[0188] According to the proportions (parts by mass) shown in Table 2, (A) curcumin, (B) sucrose fatty acid ester SE-SS, (C) HPC, and solvent were prepared in a total of 40 g. The preparation of the solution, distillation of the solvent, and pulverization using a mortar and pestle were performed using curcumin, HPC, and solvent in the same manner as in Comparative Example 4. The powder of sucrose fatty acid ester SE-SS was added to the obtained powder and mixed on a pharmaceutical packaging paper to obtain the solid composition of Example 2.
[0189] For the solid composition of Comparative Example 4, X-ray diffraction (XRD) was performed as an evaluation of amorphization. Furthermore, for the solid compositions of Examples 2 and Comparative Examples 4-5, dissolution tests were performed as an evaluation of solubility in water. These evaluation methods are as described above. It should be noted that, regarding the amorphization evaluation of the solid composition of Example 2, since it was obtained by simply mixing sucrose fatty acid esters with powder prepared in the same manner as Comparative Example 4, the same evaluation method as Comparative Example 4 was used. Furthermore, regarding the amorphization evaluation of the solid composition of Comparative Example 3, since it was obtained by simply mixing sucrose fatty acid esters and water-soluble polymers with the solid composition of Comparative Example 1, the same evaluation method as Comparative Example 1 was used.
[0190] [Table 2]
[0191]
[0192] In Comparative Example 4, a solid composition was prepared by dissolving curcumin and HPC together in a solvent, and then removing the solvent from the solution. In the solid composition of Comparative Example 4, as... Figure 3 As shown, the XRD pattern does not show characteristic peaks for curcumin, indicating that curcumin is in an amorphous state. Therefore, the solid composition of Comparative Example 4 is a solid dispersion containing amorphous curcumin. Although Comparative Example 4 is a solid dispersion, as shown in Table 2, curcumin exhibits poor solubility in water.
[0193] In Comparative Example 5, curcumin, sucrose fatty acid ester SE-SS and HPC were mixed in powder form. Simply mixing these three ingredients in powder form did not improve the solubility of curcumin in water.
[0194] In contrast, in Example 2, sucrose fatty acid ester SE-SS was powdered into a solid dispersion containing curcumin and HPC by post-mixing, thereby significantly improving the solubility in water not only compared to Comparative Example 1 and Comparative Example 5 which were in a crystalline state, but also compared to Comparative Example 4 which was a solid dispersion.
[0195] [Comparative Example 6]
[0196] Hesperidin (HPT) powder was used directly as the solid composition of Comparative Example 6.
[0197] [Comparative Example 7]
[0198] Prepare 40g of hesperidin (HPT), a water-insoluble organic compound (A), HPC, a water-soluble polymer (C), and a solvent, according to the proportions (parts by mass) shown in Table 3 below. The hesperidin and solvent are placed into a 50mL spiral tube, and then subjected to (1) heating treatment by immersing the spiral tube in a 75°C hot water bath for 4 minutes, and (2) ultrasonic treatment by immersing the spiral tube in a 50°C bath of a small ultrasonic device (manufactured by Yamato Scientific Co., Ltd., "BRANSON 2210") for 4 minutes (select "SET SONICS min" and turn it on). Repeat steps (1) and (2) until the hesperidin is completely dissolved. While stirring the resulting solution with a rotor, add HPC and stir until dissolved. Distill off the solvent from the resulting solution using an evaporator. The solvent was distilled off to almost nothing by reducing the pressure to 160 hPa at 75°C using an evaporator, and then further reduced to 60–90 hPa for 10–50 minutes, followed by 3–20 hPa for another 10–50 minutes. The solid material adhering to the wall of the flask was scraped off with a spatula and pulverized using an agate mortar to obtain the solid composition of Comparative Example 7. As described below, the solid composition of Comparative Example 7 is a solid dispersion.
[0199] [Example 3]
[0200] Prepare 40g of (A) hesperidin, (B) sucrose fatty acid ester SE-SS, (C) HPC, and solvent according to the proportions (parts by mass) shown in Table 3. The preparation of the solution, distillation of the solvent, and pulverization using a mortar and pestle were performed using hesperidin, HPC, and solvent in the same manner as in Comparative Example 7. Add the powder of sucrose fatty acid ester SE-SS to the obtained powder, mix on a pharmaceutical packaging paper, and obtain the solid composition of Example 3.
[0201] For the solid compositions of Comparative Examples 6 and 7, X-ray diffraction (XRD) was performed as an evaluation of amorphization. The evaluation method is as described above. Furthermore, for the solid compositions of Example 3 and Comparative Examples 6 and 7, dissolution tests were performed as an evaluation of their solubility in water. The evaluation method is as described below. It should be noted that, regarding the amorphization evaluation of the solid composition of Example 3, since it was obtained by simply mixing sucrose fatty acid esters in a powder prepared in the same manner as Comparative Example 7, the same evaluation method as for Comparative Example 7 was used.
[0202] [Dissolution Test: Dissolution Amount]
[0203] The filling amount of the solid composition into the gelatin capsules was calculated to be 8 mg based on hesperidin. Additionally, the mobile phase used in the HPLC was a mixture of acetonitrile / 10 mM ammonium acetate aqueous solution, and the wavelength was 289 nm. The dissolution amount was determined in the same manner as for curcumin.
[0204] [Table 3]
[0205]
[0206] In Comparative Example 6, such as Figure 4 As shown in the XRD pattern, characteristic peaks of hesperidin are present. Therefore, hesperidin is in a crystalline state. As shown in Table 3, it exhibits poor solubility in water during the dissolution test.
[0207] In Comparative Example 7, a solid composition was prepared by removing the solvent from a solution obtained by dissolving hesperidin and HPC together in a solvent. In the solid composition of Comparative Example 7, as... Figure 5 As shown, the XRD pattern does not show the characteristic peaks of hesperidin, indicating that hesperidin is in an amorphous state. Therefore, the solid composition of Comparative Example 7 is a solid dispersion containing amorphous hesperidin. Although Comparative Example 7 is a solid dispersion, hesperidin has poor solubility in water.
[0208] In contrast, in Example 3, sucrose fatty acid ester SE-SS was powdered into a solid dispersion containing hesperidin and HPC by post-mixing, thereby significantly improving the solubility in water not only compared to Comparative Example 6 which was in a crystalline state, but also compared to Comparative Example 7 which was a solid dispersion.
[0209] [Comparative Example 8]
[0210] 1 g of astaxanthin and 199 g of chloroform were added to a culture medium bottle and treated in a 60°C hot water bath for 4 hours, followed by aging at room temperature for 3 nights, and then further treated in a 60°C hot water bath for 1 hour to dissolve and isomerize the astaxanthin, yielding a chloroform solution of astaxanthin. 80 g of the obtained chloroform solution of astaxanthin was distilled off under reduced pressure at 55°C until the solvent was almost completely removed, then dried at 60–90 hPa for 30 minutes, and further dried at 3–20 hPa for 30 minutes to obtain a solid. The obtained solid was pulverized using an agate mortar to obtain the solid composition of Comparative Example 8.
[0211] [Comparative Example 9]
[0212] 80 g of the astaxanthin chloroform solution obtained in Comparative Example 8 was mixed with 1.6 g of (C)HPC while stirring with a rotor until dissolved. The resulting solution was distilled off under reduced pressure at 55°C until the solvent was almost completely removed, then dried at 60–90 hPa for 30 minutes, and further dried at 3–20 hPa for 30 minutes to obtain a solid. The obtained solid was pulverized using an agate mortar to obtain the solid composition of Comparative Example 9.
[0213] [Comparative Example 10]
[0214] Compared to 1 part by mass of the solid composition obtained in Comparative Example 8, 4 parts by mass of sucrose fatty acid ester SE-SS powder and 4 parts by mass of HPC powder were mixed on a pharmaceutical packaging paper to obtain the solid composition of Comparative Example 10.
[0215] [Example 4]
[0216] Compared to 5 parts by mass of the solid composition obtained in Comparative Example 9, 4 parts by mass of sucrose fatty acid ester SE-SS powder were mixed on a pharmaceutical packaging paper to obtain the solid composition of Example 4.
[0217] For the solid compositions of Comparative Examples 8-9, X-ray diffraction (XRD) was performed to evaluate amorphization. The evaluation method is as described above. Additionally, for the solid compositions of Examples 4 and Comparative Examples 8-10, dissolution tests were performed to evaluate their solubility in water. The evaluation method is as described below. It should be noted that, regarding the amorphization evaluation of the solid composition of Example 4, since it was obtained by simply mixing sucrose fatty acid esters in a powder prepared in the same manner as Comparative Example 9, the same evaluation method as Comparative Example 9 was used. Furthermore, regarding the amorphization evaluation of the solid composition of Comparative Example 10, since it was obtained by simply mixing sucrose fatty acid esters and a water-soluble polymer in the solid composition of Comparative Example 8, the same evaluation method as Comparative Example 8 was used.
[0218] [Dissolution Test: Dissolution Amount]
[0219] Add 0.4 mg of the solid composition (equivalent to astaxanthin) and 45 mL of deionized water to a 50 mL spiral tube. Mix the mixture by inverting the spiral tube 10 times every 30 minutes, and allow it to stand at 25°C for 120 minutes. Then filter through a 0.45 μm membrane filter. Dilute the filtrate twice with ethanol and filter through a 0.20 μm membrane filter. Calculate the area value of astaxanthin using HPLC. The 0.45 μm and 0.20 μm membrane filters used were the same substances as those used for curcumin. HPLC conditions were: column: octadecylsilane-bonded silica column; mobile phase: a mixture of acetonitrile / 10 mM ammonium acetate aqueous solution; wavelength: 470 nm.
[0220] [Table 4]
[0221]
[0222] In Comparative Example 8, such as Figure 6 As shown in the XRD pattern, characteristic peaks of isomerized astaxanthin are present. Therefore, isomerized astaxanthin is in a crystalline state, as shown in Table 4, and exhibits poor solubility in water during the dissolution test.
[0223] In Comparative Example 9, a solid composition was prepared by dissolving astaxanthin and HPC together in a solvent, and then removing the solvent from the solution. For the solid composition of Comparative Example 9, as... Figure 7 As shown, the XRD pattern does not show the characteristic peaks of isomerized astaxanthin, indicating that astaxanthin is in an amorphous state. Therefore, the solid composition of Comparative Example 9 is a solid dispersion containing amorphous astaxanthin. In Comparative Example 9, the solubility in water was improved compared to Comparative Example 8.
[0224] In Comparative Example 10, isomerized astaxanthin and sucrose fatty acid esters SE-SS and HPC were mixed in powder form. Simply mixing these three powders did not improve the solubility of astaxanthin in water.
[0225] In contrast, in Example 4, sucrose fatty acid ester SE-SS was powdered and mixed into a solid dispersion containing isomerized astaxanthin and HPC. As a result, the solubility in water was significantly improved not only compared to Comparative Example 8 and Comparative Example 10, which were in a crystalline state, but also compared to Comparative Example 9, which was a solid dispersion.
[0226] [Example 5 and Comparative Examples 11-13]
[0227] Except for replacing hesperidin with myricetin (MIR), the same procedures were followed as in Example 3 and Comparative Example 7 to obtain the solid compositions of Example 5 and Comparative Example 12. In Comparative Example 11, myricetin powder was used directly as the solid composition. In Comparative Example 13, 1 part by weight of myricetin powder, 4 parts by weight of sucrose fatty acid ester SE-SS powder, and 4 parts by weight of HPC powder were mixed on a pharmaceutical packaging paper to obtain a solid composition.
[0228] For the solid compositions of Comparative Examples 11 and 12, X-ray diffraction (XRD) was performed to evaluate amorphization. The evaluation method is as described above. Additionally, for the solid compositions of Example 5 and Comparative Examples 11-13, dissolution tests were performed to evaluate their solubility in water. The evaluation method is as described below. It should be noted that, regarding the amorphization evaluation of the solid composition of Example 5, since it was obtained by simply mixing sucrose fatty acid esters in a powder prepared in the same manner as Comparative Example 12, the same evaluation method as Comparative Example 12 was used. Furthermore, regarding the amorphization evaluation of the solid composition of Comparative Example 13, since it was obtained by simply mixing sucrose fatty acid esters and a water-soluble polymer in a powder prepared in Comparative Example 11, the same evaluation method as Comparative Example 11 was used.
[0229] [Dissolution Test: Dissolution Amount]
[0230] The filling amount of the solid composition into gelatin capsules was calculated to be 8 mg based on myricetin. The HPLC conditions were performed at a wavelength of 371 nm. The dissolution amount was determined in the same manner as for curcumin.
[0231] [Table 5]
[0232]
[0233] In Comparative Example 11, such as Figure 8 As shown in the XRD pattern, characteristic peaks of myricetin are present. Therefore, myricetin is in a crystalline state, as shown in Table 5, and exhibits poor solubility in water during the dissolution test.
[0234] In Comparative Example 12, a solid composition was prepared by dissolving myricetin and HPC together in a solvent, and then removing the solvent from the solution. In the solid composition of Comparative Example 12, as... Figure 9 As shown, the XRD pattern does not show the characteristic peaks of myricetin, indicating that myricetin is in an amorphous state. Therefore, the solid composition of Comparative Example 12 is a solid dispersion containing amorphous myricetin. In Comparative Example 12, although it was amorphized, the solubility of myricetin in water was not improved.
[0235] In contrast, in Example 5, sucrose fatty acid ester SE-SS was powdered and then mixed with a solid dispersion containing myricetin and HPC. This significantly improved the water solubility of myricetin compared to Comparative Examples 11 and 12. While an improvement in water solubility of myricetin was also observed in Comparative Example 13, where only myricetin, sucrose fatty acid ester SE-SS, and HPC were powdered, the superior water solubility of Example 5 was particularly evident after 240 minutes.
[0236] [Comparative Example 16]
[0237] The proportions (parts by mass) are shown in Table 6 below. One part by mass of curcumin (CUR) and 36 parts by mass of acetone were placed in a pressure-resistant bottle and stirred until dissolved. Four parts by mass of HPMCAS, a water-soluble polymer (C), were added to the resulting solution and dissolved. Then, nine parts by mass of water were added and stirred. The resulting solution was spray-dried using a spray dryer to distill off the solvent and recover the powder. The resulting powder was then dried under reduced pressure. Reduced pressure drying was performed using an oil pump for 6 hours under total reduced pressure. After reduced pressure drying, the solid composition of Comparative Example 16 was obtained by passing the powder through a stainless steel sieve with a mesh size of 1.0 mm.
[0238] [Comparative Example 17]
[0239] One part by weight of curcumin powder (crushed with an agate mortar), two parts by weight of sucrose fatty acid ester SE-SS powder, and four parts by weight of HPMCAS powder (crushed with an agate mortar) were mixed on a medicine packaging paper to obtain the solid composition of Comparative Example 17.
[0240] [Example 6]
[0241] Compared to 5 parts by mass of the solid composition obtained in Comparative Example 16, 2 parts by mass of sucrose fatty acid ester SE-SS powder were mixed on a pharmaceutical packaging paper to obtain the solid composition of Example 6.
[0242] [Example 7]
[0243] The proportions (parts by mass) are shown in Table 6 below. One part by mass of curcumin (CUR) and 36 parts by mass of acetone were placed in a pressure-resistant bottle and stirred until dissolved. Four parts by mass of HPMCP, a water-soluble polymer (C), were added to the resulting solution and dissolved. Then, nine parts by mass of water were added and stirred. The resulting solution was spray-dried using a spray dryer to distill off the solvent and recover the powder. The resulting powder was then subjected to vacuum drying. Vacuum drying was performed using an oil pump under total reduced pressure for 6 hours. After vacuum drying, the powder was passed through a stainless steel sieve with a mesh size of 1.0 mm. Two parts by mass of sucrose fatty acid ester SE-SS powder were mixed with five parts by mass of the resulting powder on a pharmaceutical packaging paper to obtain the solid composition of Example 7.
[0244] For the solid composition of Comparative Example 16 and the powder in Example 7 before the addition of sucrose fatty acid ester (the powder obtained by passing through a sieve after vacuum drying as described above), X-ray diffraction (XRD) was performed as an evaluation of amorphization. The evaluation method is as described above. It should be noted that, regarding the solid composition of Example 6, since it was obtained by simply mixing sucrose fatty acid ester in the powder prepared in the same manner as Comparative Example 16, the same evaluation as Comparative Example 16 was used. In addition, regarding the solid composition of Comparative Example 17, since it was obtained by simply mixing sucrose fatty acid ester and water-soluble polymer in the solid composition of Comparative Example 1, the same evaluation as Comparative Example 1 was used.
[0245] For the solid compositions of Examples 6, 7, 1, 16, and 17, a dissolution test was performed to evaluate their solubility in water. The evaluation method is described below.
[0246] [Dissolution Test: Dissolution Amount]
[0247] As a dissolution test apparatus, the "NTR-6600AST" manufactured by Toyama Sangyo Co., Ltd. was used. 900 mL of the second dissolution test solution (manufactured by Fuji Film and Wako Pure Chemicals Co., Ltd.) was added to this container and stirred overnight at a water temperature of 37℃±0.2℃ for degassing. Gelatin capsules ("HF Capsules" manufactured by Matsuya Co., Ltd.) filled with a solid composition equivalent to 15 mg of curcumin were placed in a sedimentation tablet and then placed in a glass dish. After a specified time, samples were taken from the container through a 100 μm filter and filtered through a 0.45 μm membrane filter. The specified time was set at 30 minutes, 60 minutes, and 120 minutes. The filtrate was diluted twice with ethanol, filtered through a 0.20 μm membrane filter, and curcumin was quantified by HPLC. Three measurements were performed on each solid composition, and the average was taken, rounded to the third decimal place to determine the dissolution amount. As the aforementioned 100μm filter, the "Porous Pre-Filter Poro Filter30" manufactured by Toyama Sangyo Co., Ltd. (filter material: ultra-high molecular weight polyethylene, mesh size: 100μm) was used. As the aforementioned 0.45μm membrane filter, the "25HP045AN" manufactured by ADVANTEC Co., Ltd. (filter material: hydrophilic PTFE, mesh size: 0.45μm) was used. Furthermore, as the 0.20μm membrane filter, the "13HP020AN" manufactured by ADVANTEC Co., Ltd. (filter material: hydrophilic PTFE, mesh size: 0.20μm) was used. HPLC conditions were: column: octadecylsilane column; mobile phase: a mixture of acetonitrile / 10mM ammonium acetate aqueous solution; wavelength: 430nm.
[0248] [Table 6]
[0249]
[0250] In Comparative Example 16, a solid composition was prepared by dissolving curcumin and HPMCAS together in a solvent, and then removing the solvent from the solution. In the solid composition of Comparative Example 16, as... Figure 10 As shown, the XRD pattern does not show the characteristic peaks of curcumin, indicating that curcumin is in an amorphous state. Therefore, the solid composition of Comparative Example 16 is a solid dispersion containing amorphous curcumin. As shown in Table 6, in Comparative Example 16, the solubility in water was improved compared to Comparative Example 1.
[0251] In Comparative Example 17, curcumin, sucrose fatty acid ester SE-SS, and HPMCAS were mixed into powder. Simply mixing these three into powder did not improve the solubility of curcumin in water.
[0252] In contrast, in Example 6, sucrose fatty acid ester SE-SS was powdered by post-mixing in a solid dispersion containing curcumin and HPMCAS. As a result, the solubility in water was significantly improved not only compared to Comparative Example 1 and Comparative Example 17 which were in a crystalline state, but also compared to Comparative Example 16 which was a solid dispersion.
[0253] In Example 7, as Figure 11 As shown, no characteristic peaks of curcumin were observed in the XRD pattern of the powder before the addition of sucrose fatty acid esters. Therefore, it can be concluded that in Example 7, where only sucrose fatty acid esters were mixed into the powder, curcumin was also in an amorphous state. In Example 7, sucrose fatty acid esters SE-SS were mixed into the powder via post-mixing in a solid dispersion containing curcumin and HPMCP, resulting in a significant improvement in water solubility compared to Comparative Examples 1 and 17. Furthermore, oral formulations require a rapid increase in dissolution rate; as a result, the initial dissolution rate in Example 7 was significantly improved compared to Comparative Example 16.
[0254] It should be noted that the various numerical ranges described in this specification can be arbitrarily combined with their upper and lower limits, and all combinations thereof are described in this specification as the preferred numerical ranges. Furthermore, the description of the numerical range "X~Y" refers to values above X and below Y.
[0255] The foregoing has described several embodiments of the present invention, but these embodiments are given by way of example only and are not intended to limit the scope of the invention. These embodiments can be implemented in various other ways, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments, as well as their omissions, substitutions, and modifications, are included in the scope and spirit of the invention, and are also included in the scope of the invention as described in the claims and its equivalents.
Claims
1. A solid composition, characterized in that, It contains in a mixed state: A solid dispersion comprising a water-soluble polymer as an inert carrier, wherein a crystalline, water-insoluble organic compound is dispersed in the water-soluble polymer in an amorphous state; and Sucrose fatty acid esters, wherein the proportion of monoesters in the sucrose fatty acid esters is 85% or more by mass.
2. The solid composition according to claim 1, wherein, The water-insoluble organic compound is at least one selected from the group consisting of curcuminoids, flavonoids, phenylpropanoids, stilbenes, phenolic acids, carotenoids, retinoids, steroids, alkaloids, ceramides, and limonenes.
3. The solid composition according to claim 1, wherein, The water-insoluble organic compound is at least one selected from the group consisting of curcuminoids, flavanones, flavonols, lignans, coumarins, stilbenes, phenolic acids, lutein, retinoids, phytosterols, alkaloids, glucosylceramides, and limonenes.
4. The solid composition according to claim 1, wherein, The water-soluble polymer comprises at least one selected from the group consisting of cellulose ethers, cellulose esters, homopolymers of N-vinyl lactams, copolymers of N-vinyl lactams, polyalkylene glycols, polyepoxides, and poly(meth)acrylates.
5. The solid composition according to claim 1, wherein, The mass ratio of the sucrose fatty acid ester to the water-insoluble organic compound is 0.2 to 30.
6. The solid composition according to claim 1, wherein, The mass ratio of the water-soluble polymer to the sucrose fatty acid ester is 0.1 to 10.
7. The solid composition according to claim 1, wherein, The mass ratio of the sucrose fatty acid ester to the solid dispersion is 0.1 to 3.
8. An oral composition, characterized in that, Contains a solid composition according to any one of [1] to [7].
9. A method for manufacturing a solid composition, characterized in that, Include: Using a crystalline, water-insoluble organic compound and a water-soluble polymer, a solid dispersion is obtained in which the water-insoluble organic compound is dispersed in the water-soluble polymer in an amorphous state; and The solid dispersion is mixed with a sucrose fatty acid ester in a ratio of 85% by mass or more of the monoester.
Citation Information
Patent Citations
Polyphenol-containing solid composition
WO2017061627A1